2023
DOI: 10.3991/ijet.v18i05.35959
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Twitter Sentiment Analysis for Moroccan Universities using Machine Learning and Big Data Technologies

Abstract: In recent years, sentiment analysis (SA) has raised the interest of researchers in several domains, including higher education. It can be applied to measure the quality of the services supplied by the higher education institution and construct a university ranking mechanism from social media like Twitter. Hence, this study presents a novel system for Twitter sentiment prediction on Moroccan public universities in real-time. It consists of two phases: offline sentiment analysis phase and real-time prediction ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…A similar observation was made in the comparison of SVM and Naï ve Bayes on two different datasets including IMDB and Twitter, and the findings showed that SVM performed better with 83% accuracy on IMDB and 82% on Twitter [19]. Moreover, the sentiments of people towards Moroccan universities were assessed using RF, MNB, LR DT, SVM, and XGboost, as well as the results indicated that the highest accuracy at 98% [20]. Another sentiment analysis was also conducted on a marketplace dataset using naï ve Bayes and random forest and the highest accuracy was achieved by Naï ve Bayes at 87% [21].…”
Section: Introductionsupporting
confidence: 67%
“…A similar observation was made in the comparison of SVM and Naï ve Bayes on two different datasets including IMDB and Twitter, and the findings showed that SVM performed better with 83% accuracy on IMDB and 82% on Twitter [19]. Moreover, the sentiments of people towards Moroccan universities were assessed using RF, MNB, LR DT, SVM, and XGboost, as well as the results indicated that the highest accuracy at 98% [20]. Another sentiment analysis was also conducted on a marketplace dataset using naï ve Bayes and random forest and the highest accuracy was achieved by Naï ve Bayes at 87% [21].…”
Section: Introductionsupporting
confidence: 67%
“…Support vector machines obtained the best results of machine learning methods with an accuracy of 0.986 and F1 value of 0.988. Lasri et al [10] applied six different machine learning methods (Random Forest, multinomial Naive Bayes classifier, Logistic Regression, Decision Tree, Linear Support Vector classifier, and Extreme Gradient Boosting) to classify tweets collected from Twitter about the University of Morocco into three labels (positive, negative, and neutral). The results showed that the accuracy of random forest classifier was up to 90%, and the classification performance was the best among the six machine learning methods.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…The prediction models were validated through a confusion matrix and metrics such as accuracy, recall, precision, F1-score, ROC curve, the area under the curve (AUC), and the Kappa coefficient. The definitions and formulas of each metric can be seen in detail in [35] [36]. The most relevant for this study are defined in the next section.…”
Section: Validation and Interpretationmentioning
confidence: 99%